'Absent fathers', and children's social and emotional learning: an exploration of the perceptions of 'positive male role models' in the primary school sector. Issue 2 (17th February 2018) - Wood, Peter; Brownhill, Simon
ABSTRACT: This paper focuses on the testimonies of three male primary school staff members who utilised social and emotional learning (SEL) in their everyday practice within their respective schools. The data, collected through individual interviews, illustrate how these three men interpreted SEL, and their role in the development of children's social, emotional and behavioural (SEB) skills, in response to their perceptions of pupils' home-life. In particular, the sample identified the children's fathers' perceived ability/inability as a main cause of pupils' SEB deficiencies. Consequently, the three male staff members maintained that in order to advocate and encourage alternative, appropriate behaviours, they should act as 'replacement fathers' and become 'role models'. The findings contribute to existing debates relating to the notion of 'positive male role models' in primary schools and the propensity for staff to engage in parental blame. The implications of these findings are discussed, and suggestions that call for a more democratic and cooperative exchange of knowledge between parents and teachers are made.